Rusya’da İslamiyet: geçmiş, bugün ve gelecek - Akhmetova, Elmira (Yeni Türkiye Stratejik Araştırma Merkezi, 2017)
This article in Turkish called "Islam in Russia: History, Today and Future" discusses the role of Islam in building Russian society and nation. It discusses how Islam did spread in Russian territory since 10th century, and also the status of Islam today.